The expression pattern of immunity-related genes in the immunized black soldier fly, Hermetia illucens (Diptera: Stratiomyidae) - Youngwoo CHO; Saeyoull CHO (European Journal of Entomology)
After immunizing black soldier fly (Hermetia illucens) larvae using Gram-negative (Escherichia coli) and Gram-positive (Bacillus thuringiensis, Bt) bacteria, we compared expression patterns across the whole genome. Compared to a control group treated with PBS buffer, the group immunized using Bt showed significant differences in the expression patterns of 2,312 genes. Similarly, the group immunized using E. coli showed significant differences in the expression patterns of 2,251 genes compared to the control. The groups immunized with E. coli and Bt both showed overexpression of genes involved in the extracellular region, serine-type endopeptidase activity, and neuropeptide signaling pathways, including genes related to the Toll pathway. In other words, the immune response of black soldier flies involves the simultaneous expression of innate immunity-related genes, irrespective of the type of bacteria. This is determined to be because, rather than showing a specific immune response, the flies depend on responding rapidly based on high expression levels.